REKONSTRUKSI AKSIOLOGI ILMU: INTEGRASI ETIKA DAN TANGGUNG JAWAB MORAL DALAM PRAKTIK KEILMUAN MODERN - Irpan Hilmi; Naih Nurjanah; Supiana (STKIP Subang, 2026)
This study aims to reconstruct the concept of the axiology of science through the integration of ethical values and moral responsibility within modern scientific practice, as a response to the problem of scientific neutrality and the negative impacts of the development of science and technology. The research employs a qualitative method with a library research approach, analyzing primary and secondary sources in the philosophy of science, ethics, and relevant contemporary thought. Data analysis is conducted using descriptive-analytical and critical methods to identify the limitations of classical axiological paradigms and to formulate a more integrative conceptual framework. The findings indicate that the paradigm of value-neutral science is no longer relevant in the modern context, thereby necessitating a reconstruction of axiology that positions ethics as an inherent foundation in both the production and application of scientific knowledge. The integration of ethics and the moral responsibility of scientists is essential to ensure that science is oriented toward human welfare and the sustainability of life. Thus, the reconstruction of the axiology of science contributes to the development of a more humane, responsible, and civilized scientific practice.